The role of place-based factors and other social determinants of health on adverse post-sepsis outcomes: a review of the literature - Ehrman, Robert R.; Malik, Adrienne N.; Haber, Brian D.; Glassman, Seth R.; Bowen, Cassidy A.; Korzeniewski, Steven J.; Bauer, Samantha J.; Sherwin, Robert L. (Frontiers in Disaster and Emergency Medicine, 2024)
Sepsis remains a common and costly disease. With early recognition and guideline-based treatment, more patients are surviving to hospital discharge. Many survivors experience adverse health events in the months following discharge, while others suffer long-term physical and cognitive decline. Social, biological, and environmental factors affect all aspects of the disease process, from what pathogens one is exposed to, how/if disease develops, what avenues are available for treatment, as well as short-and long-term sequelae of survival.Disparities in sepsis care exist at all stages of a patient's clinical course, but increased survivorship has highlighted the extent to which Social Determinants of Health (SDoH) influence post-discharge adverse events. Despite increased interest in the last decade, a nuanced understanding of causal relationships remains elusive. This is due to several factors: the narrow range of social determinants of health (SDoH) variables typically studied, the inconsistent and non-standardized methods of documenting and reporting SDoH, and the inadequate acknowledgment of how social, environmental, and biological factors interact. Lack of clear understanding of how SDoH influence post-discharge outcomes is an obstacle to development and testing of strategies to mitigate their harms.This paper reviews the literature pertaining to the effects of SDoH on post-discharge outcomes in sepsis, highlights gaps therein, and identifies areas of greatest need for improving the quality and impact of future investigations.